2013
DOI: 10.4172/2167-7182.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Depression among Nepalese Rai Older Adults

Abstract: Introduction: Depression is a common public health issue with the increasing life expectancy worldwide and depression is associated with morbidity as well as disability among the elderly. There are very few studies related with depression among elderly from developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
0
17
2
Order By: Relevance
“…Our study found no significant gender differences in prevalence rates of depression which mirrors similar findings in Iran (Majidi et al, 2011). It does however contradict findings from another study conducted in Nepal by Chalise and Rai (2013) that reported female gender as a major predictor of depression. A possible explanation for this difference may be that their study was focused on one rural ethnic group whereas our study sample included participants drawn from diverse backgrounds, castes and ethnicities from semi-urban communities.…”
Section: Predictors Of Depressioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study found no significant gender differences in prevalence rates of depression which mirrors similar findings in Iran (Majidi et al, 2011). It does however contradict findings from another study conducted in Nepal by Chalise and Rai (2013) that reported female gender as a major predictor of depression. A possible explanation for this difference may be that their study was focused on one rural ethnic group whereas our study sample included participants drawn from diverse backgrounds, castes and ethnicities from semi-urban communities.…”
Section: Predictors Of Depressioncontrasting
confidence: 99%
“…The prevalence estimated by our study is more than twice that of a previous Nepalese study on older adults conducted in a single ethnic group in an urban setting in the Kathmandu Valley (Chalise & Rai, 2013). Although that study used the long version GDS 30 whereas our used the GDS 15 , both of these tools have high correlation and are therefore appropriate measures of depression in community settings in Nepal (Gautam & Houde, 2011).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…14 Another study by Giri M also found the prevalence rate of 24.3% in China. 13 A contradicting finding to the present study was that only 29.7% of the geriatric reported of depression which was conducted in Kathmandu by Chalise HN and Laxmi Rai S. 23 On the contrary, a study done by Nepal S, Sapkota N, Kumar R, Deo BK, Mishra S reported that depression was the most common psychiatric diagnosis among geriatric population. 19 In associative result, significant associations were found between education level and Mild-Cognitive-Impairment score.…”
Section: Correlation Between Mild-cognitive-impairment (Moca) Score Acontrasting
confidence: 90%
“…25 The prevalence of depression among the Nepalese Rai older adults was 29.7%. 26 The prevalence of depression was 51.3% in geriatric home in Kathmandu valley. 27 The study revealed that 16.70% of health workers (both male and female) were depressed and sex was found to be a determinant factor for depression in working place (p <0.05) where male were supposed to be three times at a higher risk than females.…”
Section: Discussionmentioning
confidence: 98%